Mother's Knowledge About Giving the Rotavirus Vaccine in Preventing Diarrhea in Children Aged 0-1 Years: The study was conducted in the Sakura Room Buleleng District Hospital in 2024 - Ketut Resmiasih; Gusti Ayu Tirtawati; Made Widi Gunapria Darmapatni (Sean Institute, 2025)
Diarrhea is the second leading cause of death after pneumonia and is the main cause of dehydration in children. The aim of the research was to determine the level of knowledge of mothers regarding administering the rotavirus vaccine in preventing diarrhea in children aged 0-1 years. This type of research is descriptive with a cross-sectional study approach. The population was all 38 mothers of children aged 0-1 years who experienced diarrhea. The sampling method is non-probability sampling, namely total sampling. The data collected is primary data. The data collection tool is a questionnaire. The research results showed that the majority of respondents were aged 20-35 years (80.2%), 44.7% of respondents had two children. As many as 60.5% of respondents had secondary education, 60.5% did not work. The results of the descriptive analysis showed that 24 mothers (63.2%) had sufficient knowledge, 8 mothers (21.1%) had good knowledge, 6 mothers (15.8%) had poor knowledge. The results of the cross tabulation showed that 21 mothers (67.7%) with sufficient knowledge were aged 20-35 years, 16 mothers (69.5%) with sufficient knowledge had secondary education and 16 mothers (69.6%) with sufficient knowledge were not working. . It can be concluded that the majority of respondents have sufficient knowledge. Based on cross tabulation, respondents with sufficient knowledge were aged 20-35 years, respondents with sufficient knowledge had at least a high school education and the majority did not work. It is hoped that health services will be more proactive in providing health education to mothers of toddlers regarding rotavirus vaccination.